Preparation of iron-containing sulfenyl complex and application of iron-containing sulfenyl complex in specific detection of organic amine

Through the iron-sulfur polyamine-specific identification sensor, the assembly uses the transition mode from order to order, and solves the problem of temperature, reaction time and pH dependence in the existing polyamine detection methods, achieving rapid, simple and Specific polyamine detection improves detection efficiency and sensitivity.

CN119219709APending Publication Date: 2024-12-31DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310775739.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing polyamine detection methods require specific temperatures, reaction times and pH values, and it is difficult to achieve efficient assembly transitions from orderly to disorder, limiting detection efficiency and sensitivity.

Method used

Using a polyamine-specific identification sensor with iron-sulfur group as the main body, a variety of sulfur-bridged metal complexes are constructed through the coordination of sulfur ligands, and the detection mode of polyamine is driven by the assembly from order to order. Achieve fast, simple, cyclable and specific detection.

Benefits of technology

It realizes rapid, simple, cyclable and specific detection of polyamines, improves detection efficiency and sensitivity, and provides an environmentally stable detection solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219709A_ABST
    Figure CN119219709A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of an iron-containing sulfenyl complex and application of the iron-containing sulfenyl complex in specific detection of organic amine. According to the complex, mononuclear iron is used as a precursor and reacts with different metal salts in different organic solvents, and complexes with two configurations are selectively obtained. According to the present invention, the rapid specific recognition performance of the iron-sulfur series sensor on the polyamine is verified by using the iron-sulfur series sensor as the main body, using the polyamine, the monoamine and other interfering compounds containing different substituent groups as the object and using the complex as the main body, and the sensing mechanism is explored in detail; according to the invention, a series of double / multi-metal sensors are constructed by taking bionic iron-sulfur groups as precursors for the first time, specific detection of polyamine is realized by utilizing coordination difference acting force between an object and metal and a response mode of conversion from order to order of a rare assembly, and a new thought is provided for application of an iron-sulfur complex in the field of separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for specific detection of polyamines driven by the transition of an assembly from order to order based on iron-sulfur groups, a series of sensors for specific detection of polyamines are constructed using iron-sulfur groups, and a new mechanism for detection of polyamines driven by the transition of an assembly from order to order during the detection process is proposed, which belongs to the field of analytical chemistry. Background Art

[0002] The detection of organic amines has received special attention due to their key roles from organic synthesis to environmental monitoring. Typically, organic amines are highly toxic, harmful, colorless, and have no chromophores, which makes them difficult to distinguish directly by visual inspection. Among them, polyamines are involved in a variety of functional applications, such as analytical testing, drug development, chemotherapy, and bioregulation, which makes the determination of polyamines very important, especially the detection of synthetic polyamines. For example, the melamine incident, as a scandal in infant formula, led to the hospitalization and even death of tens of thousands of children, which also sounded the alarm for the safety of the global food chain. So far, in the field of polyamine detection, scientists have developed various sensing materials, including molecular probes, chemical sensors, and nanosensors, but the detection system usually requires specific temperature, reaction time, and pH value. From the perspective of sensing mechanism, the above sensing systems can be divided into two types of response modes: one is the direct binding between the sensor and the analyte, including irreversible covalent bonds and reversible non-covalent bonds; the other is the displacement reaction between the indicator (ligand) and the target analyte. The above two detection modes mainly focus on the interaction at the molecular level. In contrast, few literature reports on chemical sensing based on molecular self-assembly. Since the formation or destruction of ordered assemblies during the sensing process is a transformation at the supramolecular level, such significant changes can greatly promote the sensing efficiency, but the entire process is difficult to be precisely manipulated. In addition to these order-to-disorder transitions, in this paper, we innovatively proposed a selective polyamine detection mode driven by the order transition of assemblies based on an iron-sulfur platform.

[0003] Iron-sulfur complexes are a series of metal complexes prepared by the inspiration of enzyme cofactors. They play an important role in various fields, such as catalysis and electron transfer, due to their unique activity and selectivity. In recent decades, various iron-sulfur complexes have been developed, and their core skeletons are composed of iron atoms, sulfur ligands and auxiliary ligands. However, these synthetic highly active model complexes usually have the characteristics of low coordination number and low metal valence state. Their inherent fragility and reactivity to air and water determine that all related operations should be carried out under strict anhydrous and oxygen-free conditions, which greatly limits their practical application in the environment. Nevertheless, the unique redox and coordination properties of iron-sulfur provide prospects for the development of unknown applications in sensing detection, and the key is to design and synthesize structurally stable iron-sulfur systems. Summary of the invention

[0004] The purpose of the present invention is to provide a series of polyamine specific recognition sensors based on iron-sulfur groups, using environmentally stable mononuclear iron-sulfur groups as precursors, and constructing a variety of sulfur-bridged metal complexes through the coordination of sulfur ligands. The present invention provides a specific detection method for polyamines, using different types of polyamines, monoamines and other interfering substances as objects, based on a unique detection mode driven by the transition of assemblies from order to order, to achieve rapid, simple, recyclable and specific detection of polyamines.

[0005] The present invention solves the technical problem by adopting the following technical solutions:

[0006] The present invention provides a series of iron-sulfur based sensors: mononuclear iron-sulfur complex [Cp*Fe(η 3 -tpdt)] is composed of a sterically hindered pentamethylcyclopentadiene (Cp*=η 5 -C5Me5) auxiliary ligand and a flexible structure of bis(thiothioethyl)sulfide (tpdt, S[CH2CH2S - ]2) The ligand is composed of an iron atom and has high environmental stability. Using this as a precursor, different organic solvents and reaction times are selected to achieve the preparation of other metal salts through MS d-pπ interaction. Finally, the mixed solution is filtered, washed and dried to construct a variety of sulfur-bridged metal complexes.

[0007] Using mononuclear iron as a precursor, the lone pair of electrons on the sulfur ligand are used to re-coordinate the metal complexes that can form a stable structure with the precursor. The specific steps are as follows: the mononuclear iron precursor is dissolved in a corresponding organic solvent, including dichloromethane, tetrahydrofuran, methanol, etc., and then a metal salt with a molar ratio of 1:1 or 1:0.5 to the mononuclear iron is added to the solution. The types of metal salts include zinc chloride, ferrous chloride, manganese chloride, palladium chloride, nickel chloride and cuprous chloride. After reacting at room temperature for a certain period of time, the mixed solution is filtered and dried, and the product is characterized by high-resolution mass spectrometry and hydrogen nuclear magnetic resonance. For neutral compounds, hexafluorophosphate ammonium is used to exchange negative ions.

[0008] A series of sulfur-bridged metal complexes are constructed as sensors to specifically detect polyamines. The detection process is based on the coordination differences between metal ions of different metal types and polyamines, monoamines and other non-amine substances. The detection results are characterized by different detection methods. The specific steps are as follows:

[0009] (1) Characterize the specific detection of polyamines by ultraviolet-visible absorption spectroscopy test, the steps are as follows: first, add 3 mL of 0.33 mM dichloromethane solution of the metal complex to a quartz colorimetric cell with two transparent surfaces, collect the ultraviolet-visible spectrum of the complex, then add different concentrations of polyamines (0.05, 0.1, 0.2, 0.3, 0.4, 1.0 and 2.0 mM), monoamines (1.0, 2.0, 3.0, 4.0, 5.0, 10.0 and 15.0 mM) and other interfering analytes (0.4 and 15 mM), collect the spectrum again, compare the changes in the absorption peak position and intensity in the ultraviolet-visible region before and after the addition of the analyte, and judge the specific recognition performance of the sensor for polyamines;

[0010] (2) Characterization of polyamine-specific detection by naked eye detection, the steps are as follows: first, the initial color of various complexes (0.33 mM) in dichloromethane was photographed and recorded, then representative polyamines, monoamines and interfering substances were added at a concentration of 0.4 mM, including diethylenetriamine, cyclopentane, 4,4'-bipyridine, n-propylamine and ethyl acetate, and then the color of the response mixture was photographed. By comparing the color change of the mixture before and after the addition of the object, the polyamine response effect was evaluated;

[0011] (3) The specific detection of polyamines was characterized by differential pulse voltammetry, and the steps were as follows: first, the redox peak positions of various complexes were determined by cyclic voltammetry test, and then the complexes were subjected to differential pulse voltammetry test according to the oxidation peak positions. Then, analytes with solubility of 60, 150, 300, 60, 900, 1200, 1500 and 1800 μM were added, and the intensity of the oxidation peak was detected. Finally, a standard curve was drawn according to the amplitude of the intensity change, and the responsiveness of the complex to the analyte was judged by the size of the slope.

[0012] Using a series of sulfur-bridged metal complexes as sensors, in the specific detection of polyamines, the unique detection mode based on the transition of the assembly from ordered to ordered is the key driving force. The mechanism is studied in detail through different testing methods. The specific steps are as follows:

[0013] (1) The mechanism is studied by electron spin spectroscopy, the steps are as follows: first, the complex is tested by electron spin spectroscopy to determine the single-electron state of the initial complex, then the mixed solution is tested by electron spin spectroscopy again after adding polyamine, and the single-electron state of the complex before and after the polyamine response is recorded;

[0014] (2) The mechanism is studied by cyclic voltammetry test, the steps are as follows: first, the complex is tested by cyclic voltammetry, then after adding polyamine, the mixed solution is tested again, and the changes in the peak position and peak intensity of the redox peak of the complex before and after the addition of polyamine are recorded to determine the changes in the system components;

[0015] (3) The mechanism was studied by NMR titration experiments, the steps are as follows: first, each complex (1.0 mM) was dissolved in different deuterated reagents and its H NMR spectrum was tested, then polyamine (1.2 mM) was added and the NMR spectrum was collected again. By judging the chemical shift and integrated area of ​​the new peak after the polyamine response, the type and specific structure of the newly generated compound were inferred;

[0016] (4) The mechanism was studied by low-field NMR testing, the steps are as follows: by collecting low-field NMR data of the complex before and after the addition of polyamine, the relaxation time of the system before and after was compared to infer the magnetic state of the newly generated system;

[0017] (5) The mechanism was studied by X-ray single crystal diffraction technology, the steps are as follows: after mixing the complex with the polyamine in a molar ratio of 1:1, the upper solution was filtered, the residue was collected and purified, and the precise structure of the new compound was determined at the molecular level by growing single crystals and testing;

[0018] (6) The mechanism is studied by dynamic light scattering test, the steps are as follows: first, the solution state of the complex is subjected to dynamic light scattering test to record the particle size of the complex, and then the particle size of the mixed solution after adding polyamine is tested, so as to judge the changes of the new system after the polyamine response at the macro level;

[0019] (7) The mechanism was studied by scanning electron microscopy. The steps are as follows: the complex and polyamine were mixed in a molar ratio of 1:1, and the mixture was placed at room temperature for about 5 minutes. Then, 20 μL of the pure complex solution and the mixed solution were respectively transferred onto a silicon wafer using a pipette and allowed to air dry naturally. The two groups of samples were then subjected to scanning electron microscopy and photoelectron spectroscopy tests. By comparing the morphological changes and elemental composition before and after the addition of polyamine, the transition process from ordered to unordered in the assembly during the polyamine response process was determined.

[0020] This invention is the first to construct a series of dual / multi-metal sensors using bionic iron-sulfur as precursors. It utilizes the coordination difference forces between the guest and the metal and the rare response mode of the assembly from ordered to ordered transition to achieve specific detection of polyamines, providing new ideas for the application of iron-sulfur complexes in the separation field. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 .Types of analytes in UV detection experiments.

[0023] Figure 2 .UV-visible absorption spectrum test;

[0024] (AE) UV-visible spectra changes of C1 (0.33 mM) after adding diethylenetriamine (A), cyclamen (B), 4,4'-bipyridine (C), n-propylamine (D) and ethyl acetate (E); (F, G) UV changes of C2 (F) and C3 (G) after adding diethylenetriamine, cyclamen, 4,4'-bipyridine, n-propylamine and ethyl acetate at a concentration of 0.4 mM, respectively; (H, I) UV changes of C4 (H) and C6 (I) after adding diethylenetriamine, cyclamen, n-propylamine and ethyl acetate at a concentration of 0.4 mM, respectively.

[0025] Figure 3 .Electrochemical data testing;

[0026] Differential pulse voltammetry (A) and cyclic voltammetry (B) tests.

[0027] Figure 4 .Scanning electron microscope images and photoelectron spectroscopy test results of complex C1 before and after responding to cyclohexine.

[0028] Figure 5 .Scanning electron microscope image of the assembly after the complex responds to polyamine;

[0029] (A–B) SEM images of C1 mixed with ethylenediamine (A) and 4,4'-bipyridine (B). (C–F) SEM images of C2 mixed with 2,2'-bipyridine (C), 4,4'-bipyridine (D), imidazole (E), and histamine (F). (G–I) SEM images of C3 mixed with diethylenetriamine (G), imidazole (H), and histamine (I).

[0030] Figure 6 .Single crystal information of complex N1;

[0031] The crystal structure of complex N1 (A) and its spatial structure in the x (B), y (C), and z (D) directions. DETAILED DESCRIPTION

[0032] To make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. The protection scope of the present invention is not limited to this, and any technician familiar with the technical field is within the technical scope disclosed by the present invention, and the technical scheme and its inventive concept of the present invention are equal or replaced, which should be covered within the protection scope of the present invention.

[0033] Experimental Materials. Some operations were performed under argon atmosphere using standard Schlenk techniques and a 100 μm argon-filled glove box. Tetrahydrofuran and dichloromethane were dried by conventional procedures and distilled under nitrogen before use. Anhydrous ferrous chloride (Aldrich), pentamethylcyclopentadiene (Energy Chemical), n-butyllithium (Heowns), bis-mercaptoethyl sulfide (Aldrich), zinc chloride (Heowns), manganese chloride (Energy Chemical), palladium chloride (Energy Chemical), nickel chloride (Aladdin), cuprous chloride (Aladdin), aluminum chloride (Macklin), titanium chloride (Macklin), vanadium chloride (Innochem), various organic amines (Aldrich), various solvents (Xilong Scientific), lanthanides (Innochem), and ammonium hexafluorophosphate (Aladdin) were obtained from commercial suppliers without further purification. Deuterated dichloromethane, deuterated acetonitrile, deuterated DMSO, and heavy water were purchased from Alfa Aesar and used as described in the literature. Molecular sieves for drying.

[0034] Experimental instruments. High-resolution mass spectrometry data were collected on a HPLC / Q-Tof mass spectrometer. Infrared spectra were collected on a NICOLETiS50 ATR spectrometer. 1 H) and carbon NMR ( 13C) Data were recorded on a Brüker 400M Ultra Shield spectrometer. Low-field nuclear magnetic resonance spectra were recorded on a Suzhou Niumag VTMR20-010V-I spectrometer. Electron spin spectrometry spectra were recorded on a JEOL JES-FE3AX spectrometer at room temperature. UV-visible spectra were recorded on a PerkinElmer Lambda 365 spectrometer. Electrochemical data were obtained on a dual-display constant potential instrument (CHI760E, Shanghai Chenhua). Dynamic light scattering data were collected on a Zetasizer Nano instrument. SEM measurements were performed on a JEOL JSM-7800F instrument, elemental composition was collected by X-ray photoelectron spectroscopy (EDS, X-Max50, Oxford), and single crystal data were collected on a Brüker SMART APEX CCD.

[0035] Example 1 Mononuclear iron complex [Cp*Fe(η 3 Preparation of β-TPdt

[0036]

[0037] Complex [Cp*Fe(η 3 -tpdt)](Cp*=η 5 -C5Me5;tpdt,S[CH2CH2S - ]2) was prepared according to the literature (Organometallics 2015, 34, 1661–1667). At 0°C, anhydrous ferrous chloride (1.90 g, 15 mmol) was added to a suspension of Cp*Li (2.14 g, 15 mmol) in THF (80 mL) and stirred at this temperature for 1 h to obtain an olive green [Cp*FeCl]2 tetrahydrofuran solution. It was cooled to -78°C and a solution of bis(2-mercaptoethyl) sulfide (2.31 g, 15 mmol) in THF (50 mL) and n The mixed solution after the reaction of BuLi (1.92g, 30mmol). The color of the solution immediately turned purple-red, and the temperature slowly rose to -30°C to obtain a purple solution. The purple solution was warmed to room temperature and stirred for 2 hours, and the mother liquor turned blue. After the solution was exposed to air for 30 seconds, the color immediately changed from blue to dark green, accompanied by the formation of yellow-white precipitates. The solvent was removed by vacuum, extracted with n-hexane, and frozen and crystallized at -30°C to obtain needle-shaped black crystals as the complex [Cp*Fe(η 3 -tpdt)] with a yield of 76%. 1H NMR (400MHz, CD2Cl2, ppm): δ-8.94 (br, 8H, tpdt-CH2), -25.63 (br, 15H, Cp*-CH3). EPR (298K): g = 2.09.

[0038] Example 2 Complex [Cp*Fe(μ-1 κ 3 SS′:2 κ 2 Preparation of SS-tpdt)ZnCl2](C1)

[0039]

[0040] In a glove box, solid zinc chloride (42 mg, 0.31 mmol) was added to the mononuclear [Cp*Fe(η 3 -tpdt)] precursor (103 mg, 0.30 mmol) was added to dichloromethane (10 mL), and the resulting solution was stirred at room temperature for about 0.5 hours. During this period, the solution gradually changed from green to purple-red. The mixture was then filtered, dried, and washed with THF (3 times × 5 mL). The obtained product [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)ZnCl2](C1, 137 mg, 0.29 mmol, yield 95%) is a dark purple crystalline powder. At room temperature, n-hexane (5 mL) was slowly added dropwise to a saturated dichloromethane solution (2 mL) of C1, and after standing for 3 days, crystals suitable for X-ray diffraction were obtained. 1 H NMR (400MHz, CD2Cl2, ppm): δ-9.91 (br, 8H, tpdt-CH2), -32.24 (br, 15H, Cp*-CH3). EPR (298K): g = 2.10.

[0041] Example 3 Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 Preparation of SS-tpdt)FeCl2](C2)

[0042]

[0043] In addition to replacing zinc chloride with an equal molar amount of ferrous chloride, [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2The synthesis path (i.e., process and conditions) of the complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)ZnCl2] is the same. The complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)FeCl2](C2, yield 90%) is a dark green crystalline powder. 1 H NMR (400MHz, CD2Cl2, ppm): δ-10.22 (br, 8H, tpdt-CH2), -21.49 (br, 15H, Cp*-CH3). EPR (298K): g = 2.02.

[0044] Example 4 Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 Preparation of SS-tpdt)MnCl2](C3)

[0045]

[0046] In addition to replacing zinc chloride with an equimolar amount of manganese chloride, [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 The synthetic route (i.e., process and conditions) of the complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)ZnCl2] is the same. The complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)MnCl2] (C3, yield 92%) is a dark purple crystalline powder. At room temperature, n-hexane (5 mL) was slowly added dropwise to a saturated dichloromethane solution (2 mL) of C3, and after standing for 3 days, crystals suitable for X-ray diffraction were obtained. 1H NMR (400MHz, CD2Cl2, ppm): δ39.38(br,4H,tpdt-CH2), 19.78(br,4H,tpdt-CH2), -21.31(br,7.5H,Cp*-CH3), -36.80(br,7.5H,Cp*-CH3). EPR(298K): g=2.08.

[0047] Example 5

[0048] Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Pd(μ-2 κ 2 SS:3 κ 3 Preparation of SSS′-tpdt)FeCp*][PF6]2(C4)

[0049]

[0050] In a glove box, solid palladium chloride (27 mg, 0.15 mmol) was added to the complex [Cp*Fe(η 3 -tpdt)] precursor (103 mg, 0.30 mmol) in methanol (10 mL) and stirred for about 2 hours, the solution gradually changed from green to brownish red. Then ammonium hexafluorophosphate (197 mg, 1.20 mmol) was added as a solid to the resulting solution, and the immediate formation of a purple precipitate was observed. The residue was collected, extracted with acetonitrile, evaporated, and washed with ether (3×5 mL). The obtained product [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Pd(μ-2 κ 2 SS:3 κ 3 SSS′-tpdt)FeCp*][PF6]2(C4,151mg,0.14mmol,yield 90%) is a dark yellow crystalline powder. 1H NMR (400MHz, CD3CN, ppm): δ-2.51(br,4H,tpdt-CH2),-3.83(br,4H,tpdt-CH2),-17.76(br,4H,tpdt-CH2),-21.95(br,4H,tpdt-CH 2),-23.68(br,15H,Cp*-CH3),-29.62(br,15H,Cp*-CH3).ESI-HRMS(m / z):calcd:395.9835;found:395.9830.EPR(298K):g=2.06.

[0051] Example 6

[0052] Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Ni(μ-2 κ 2 SS:3 κ 3 Preparation of SSS′-tpdt)FeCp*][PF6]2(C5)

[0053]

[0054] In addition to replacing palladium chloride with an equimolar amount of nickel chloride, [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Ni(μ-2 κ 2 SS:3 κ 3 The synthetic route (i.e., process and conditions) of the complex [SSS′-tpdt)FeCp*][PF6]2 is similar to that of Example 5 [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Pd(μ-2 κ 2 SS:3 κ 3 SSS′-tpdt)FeCp*][PF6]2 is the same. The complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Ni(μ-2 κ 2 SS:3 κ3 SSS′-tpdt)FeCp*][PF6]2 is a dark brown crystalline powder with a yield of 91%. 1 HNMR(400MHz,CD2Cl2,ppm): δ3.31(br,8H,tpdt-CH2),2.93(br,8H,tpdt-CH2),1.58(s,30H,Cp*-CH3).ESI-HRMS(m / z):calcd:371.9989;found:371.9991.

[0055] Example 7

[0056] Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Cu(μ-2 κ 2 SS:3 κ 3 Preparation of SSS′-tpdt)FeCp*][PF6](C6)

[0057] In addition to replacing palladium chloride with cuprous chloride, [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Cu(μ-2 κ 2 SS:3 κ 3 The synthetic route (i.e., process and conditions) of the complex [SSS′-tpdt)FeCp*][PF6] is similar to that of Example 5 [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Pd(μ-2 κ 2 SS:3 κ 3 SSS′-tpdt)FeCp*][PF6]2 is the same. The complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)Cu(μ-2 κ 2 SS:3 κ 3 SSS′-tpdt)FeCp*][PF6] is a dark purple crystalline powder with a yield of 92%. 1H NMR (400MHz, CD2Cl2, ppm): δ7.31(s,4H,tpdt-CH2),-10.94(m,4H,tpdt-CH2),-14.14(s,4H,tpdt-CH2), -20.05(s,4H,tpdt-CH2),-29.96(s,30H,Cp*-CH3).ESI-HRMS(m / z):calcd:748.9921;found:748.9923.

[0058] Example 8 Complex [(η 4 Preparation of -cyclen)ZnCl][Cl](N1)

[0059]

[0060] At room temperature, solid cyclopentane (43 mg, 0.25 mmol) was added to [Cp*Fe(μ-1 κ 3 SS′:2 κ 2 SS-tpdt)ZnCl2] (101 mg, 0.21 mmol) in dichloromethane (10 mL) solution was stirred vigorously for 10 minutes to obtain a green suspension. The reaction solution was centrifuged, the supernatant was discarded, the solid at the bottom of the centrifuge tube was washed with dichloromethane, and centrifuged again. This operation was repeated until the dichloromethane supernatant was colorless. The solid was dried to obtain a yellow solid [(η 4 -cyclen)ZnCl][Cl], the yield is 95%. At room temperature, ether (5 mL) was slowly added dropwise to a saturated methanol solution of N1 (2 mL), and after standing for 3 days, crystals suitable for X-ray diffraction were obtained. 1 H NMR(400MHz,D2O,ppm): δ3.05(s,4H,NH),2.89-2.94(m,8H,cyclen-CH2),2.75-2.81(m,8H,cyclen-CH2).13CNMR(100MHz,D2O):δ43.60(cyclen-CH2).ESI-HRMS(m / z):calcd for[N1-Cl] + :271.0668; found:271.0664.

[0061] Example 9 Complex [(η 2 Preparation of [2,2'-bipyridine)FeCl2](N2)

[0062]

[0063] Solid 2,2′-bipyridine (39 mg, 0.25 mmol) was added to [Cp*Fe(μ-1 κ 3 SS′:2 κ 2 SS-tpdt)FeCl2] (100 mg, 0.21 mmol) in dichloromethane (10 mL) was stirred vigorously for 10 minutes to obtain a dark red solution. The reaction solution was dried under vacuum to obtain a dark red solid [(η 2 -2,2'-bipyridine)FeCl2] with a yield of 93%. Ether (5 mL) was slowly added dropwise to a saturated methanol solution (2 mL) of N2 at room temperature and allowed to stand for 3 days to obtain crystals suitable for X-ray diffraction. 1 H NMR (400MHz, DMSO-d6, ppm): δ8.84(s,2H,Ar-H),8.17(s,2H,Ar-H),7.36-7.49(m,4H,Ar-H). 13 C NMR (100MHz, DMSO-d6): δ157.64,152.80,137.94,126.84,123.40.

[0064] Example 10 Complex [(η 4 Preparation of -cyclen)MnCl][Cl](N3)

[0065]

[0066] At room temperature, solid cyclopentane (43 mg, 0.25 mmol) was added to [Cp*Fe(μ-1 κ 3 SS′:2 κ 2 SS-tpdt)MnCl2] (100 mg, 0.21 mmol) in dichloromethane (10 mL) solution, vigorously stirred for 10 minutes to obtain a green suspension. The reaction solution was centrifuged, the supernatant was discarded, the solid at the bottom of the centrifuge tube was washed with dichloromethane, and centrifuged again. This operation was repeated until the dichloromethane supernatant was colorless. The solid was dried to obtain a yellow solid [(η 4 -cyclen)MnCl][Cl], the yield is 90%. At room temperature, ether (5 mL) was slowly added to a saturated methanol solution of N3 (2 mL), and after standing for 3 days, crystals suitable for X-ray diffraction were obtained. ESI-HRMS (m / z):calcd for [N3-Cl] + :262.0757; found:262.0739.EPR(298K):g=2.00.

[0067] Example 11 UV-Visible Spectroscopy Test

[0068] The response strength of the complex to the analyte can be determined by the change in the ultraviolet absorption peak of the complex after the addition of the analyte. First, 3 mL of a 0.33 mM dichloromethane solution of the metal complex was added to a quartz colorimetric cell (10 mm long, 10 mm wide, and 3.5 mL in volume) with two transparent sides, and the ultraviolet-visible spectrum of the complex was collected in the wavelength range of 200 to 900 nm. Then, the following were added: Figure 1 Different types of analytes are shown, where the final concentrations of polyamines (1-14) are 0.05, 0.1, 0.2, 0.3, 0.4, 1.0 and 2.0 mM, the final concentrations of monoamines (15-28) are 1.0, 2.0, 3.0, 4.0, 5.0, 10.0 and 15.0 mM, and the final concentrations of other interfering analytes (29-41) are 0.4 and 15 mM, and their UV spectra are recorded again. The measurement temperature is maintained at 20°C, and the upper port of the colorimetric cell is sealed with a polytetrafluoroethylene cap during the test to prevent the volatilization of dichloromethane.

[0069] By summarizing the changes in the UV-visible absorption peak positions of complexes C1-C6 before and after the addition of various analytes, the response results of complexes C1-C6 to polyamines, monoamines and interfering compounds were obtained: complexes C1 (0.33mM) and C2 (0.33mM) had a strong response to lower concentrations (0.05mM) of polyamines (the absorption peak shift range was about 15nm), and with the increase of polyamine concentrations (0.05-0.4mM), the shift amplitude of the UV absorption peak also increased (the absorption peak wavelength shifted from 553nm to 560nm), and the response to monoamines was relatively weak, and only when the monoamine concentration was greater than or equal to 2mM, the UV absorption peak had a weak The shift of the ultraviolet absorption peak is smaller than 10nm, but it has no response to interfering substances (compounds such as alcohols, aldehydes, acids, esters, thiols, amides, ketones, ethers, etc. except polyamines and monoamines) (the absorption peak wavelength does not change); C3 (0.33mM) has a strong response to low concentration (0.4mM) of polyamines and most monoamines, and the shift of the ultraviolet absorption peak is also large (the absorption peak wavelength moves from 522nm to 590nm), but has no response to interfering substances (the absorption peak wavelength does not change); C4, C5 and C6 with a concentration of 0.33mM have no response to all analytes (15mM) (the absorption peak wavelength does not change). The following are the test results of UV-visible spectra of complexes C1-C6, C4 and C6, respectively, with diethylenetriamine, cyclen and 4,4'-bipyridine as polyamine representatives, n-propylamine as monoamine representative, and ethyl acetate (EtOAc) as interfering substance representative ( Figure 2 ).Depend on Figure 2 It can be seen from A to C and 2F that for C1 and C2, after adding polyamine (0.4mM), the ultraviolet absorption peaks of C1 and C2 shifted significantly, and with the gradual increase of polyamine concentration (0.05-0.4mM), the amplitude of the absorption peak shift also gradually increased, but C1 showed a red shift (moving to a longer wavelength, from 553nm to 589nm), C2 showed a blue shift (moving to a shorter wavelength, from 640nm to 584nm), and for monoamine ( Figure 2 D and 2F), when the concentration of added was greater than 2 mM, the absorption peaks of C1 and C2 began to shift slightly (C1: from 553 nm to 564 nm; C2: from 640 nm to 634 nm), while the absorption peak did not shift after adding EtOAc ( Figure 2 E and 2F); for C3( Figure 2 G), when adding 0.4mM polyamine and monoamine, the UV absorption peak of C2 shifted significantly (from 522nm to 588nm), while the absorption peak did not shift when adding EtOAc; for C4 and C6 ( Figure 2H and 2I), the absorption peaks do not shift when polyamines, monoamines and interfering substances are added.

[0070] The above results indicate that UV-visible spectroscopy testing can reflect the response of the complex to the analyte. The greater the shift in the absorption peak of the complex after the addition of the analyte, the more sensitive the response to the analyte, thereby determining the qualitative detection of the response of complexes C1, C2 and C3 to polyamines.

[0071] Example 12 Electron Spin Spectroscopy Test

[0072] The change of the electronic spin state of the complex after the addition of the analyte is used to determine whether new products are generated. The data of the complexes C1, C2, C3 and C6 were obtained in dichloromethane solution, while the data of the complex C4 was collected in CH3CN solution, and the solubility was 10mM. These liquid samples were encapsulated in a hollow glass tube with a diameter of 1.5 mm, and then placed in a quartz tube for testing at 20°C. The test results show that the electronic spin angular momentum g values ​​of C1, C2, C3, C4 and C6 are 2.10, 2.02, 2.08, 2.06 and 2.06, respectively. The g values ​​of C1, C2 and C3 after responding to equimolar amounts of cyclopentane all become 2.09, and the g values ​​of C4 and C6 in the presence of equimolar amounts of cyclopentane do not change, indicating that C1, C2 and C3 can respond to cyclopentane, and there are new compounds ([Cp*Fe(η 3 -tpdt)]) is generated, while C4 and C6 do not respond to cyclopentane, so the g value in the electron spin spectrum test does not change. From the above results, it can be concluded that the response of the complex to the analyte can be qualitatively detected by electron spin spectrum test.

[0073] Example 13 Electrochemical Data Test

[0074] The electrochemical data were measured at 20°C in a nitrogen environment using a three-electrode system in an inert gas atmosphere. The working electrode was a glassy carbon electrode (3 mm in diameter) and the reference electrode was Ag / Ag + The electrode and the auxiliary electrode were platinum wires, which were purchased from Shanghai Yue Magnetic Electronics. The current was in μA and the potential was in V. The supporting electrolyte was 0.1 M tetrabutylammonium hexaphosphate dissolved in acetonitrile (10 mL). Using C1 (1 mM) as a template, different concentrations (0.3, 3, 30, 60, 150, 300, 600, 900, 1200, 1500 and 1800 μM) of diethylenetriamine, cyclen, 4,4'-bipyridine and n-propylamine were added. nproylamine) and recorded the corresponding differential pulse data ( Figure 3 A). The potential range is set to -0.8 to -1.2 V, and the amplitude is 0.05 V. By statistically analyzing the current values ​​corresponding to the potential of -0.96 V, linear fitting was used to develop the corresponding standard curves: diethylenetriamine: I (μA) = -0.01198C (μM) + 17.2 (R 2 =0.993); Cyclotrimethylenetetramine: I (μA) = -0.00921C (μM) + 17.6 (R 2 =0.989); 4,4'-bipyridine: I (μA) = -0.00366C (μM) + 16.2 (R 2 =0.955); n-propylamine: After adding different concentrations of n-propylamine, the current change in the differential pulse data is too small (less than 0.001μA), and there is a large error in Gaussian fitting, so it is not suitable for formulating a standard curve. By comparing the slopes of the above curves, it can be used for qualitative detection of polyamines, and can also be used for quantitative measurement of polyamines through the formulation of standard curves.

[0075] In addition, the detection process can also be qualitatively detected by cyclic voltammetry test ( Figure 3 B) where the scan rate is 50 mV·S –1 , the potential range is –1.5~1.1V. First, the cyclic voltammetry test of cyclen was performed, which showed that it did not have any redox peaks. The cyclic voltammetry test results of C1 showed that it had an oxidation peak at 0.816V and a peak at the half-wave potential E 1 / 2 = There is a pair of redox peaks at –0.957V. After adding cyclen, the oxidation peak of C1 at 0.816V almost disappears, and an obvious oxidation peak is generated at 0.073V, which corresponds to [Cp*Fe(η 3 -tpdt)], indicating that the binuclear C1 is decomposed into a mononuclear iron precursor [Cp*Fe(η 3 -tpdt)]. The above results show that by testing the cyclic voltammetry curve of C1 before and after adding the analyte, its qualitative detection of the analyte can be achieved.

[0076] Example 14 Dynamic light scattering test

[0077] The dynamic light scattering experiment can be used to test the change in particle size of the complex after the addition of polyamines. The detection temperature is 20°C, and the upper port of the cuvette is sealed with a polytetrafluoroethylene lid to prevent the volatilization of the dichloromethane solvent. Taking C1 as a template, the average particle size of a dichloromethane solution with a concentration of 0.1mM is 11nm. After the addition of cyclopentane (final concentration 0.12mM), the corresponding average particle size of the mixed solution is 602nm, indicating that after C1 reacts with cyclopentane, larger particles that are insoluble in dichloromethane are produced. The above results show that by testing the dynamic light scattering of the complex before and after the addition of the analyte, the qualitative detection of the analyte can be achieved.

[0078] Example 15 Scanning electron microscope test

[0079] At the same time, after clarifying the response mechanism of the complex to the analyte at the molecular level, we explored the mechanism at the macroscopic level. Using C1 as a template and mixing it with cyclopentane, the above series of tests proved that C1 decomposed into a mononuclear iron precursor [Cp*Fe(η 3 -tpdt)], and particles insoluble in dichloromethane were produced. The macroscopic morphology and elemental composition can be determined by scanning electron microscopy. After mixing equimolar C1 (final concentration 3.3mM) and cyclopentane (final concentration 3.3mM) in dichloromethane solution, the mixture was aspirated several times with a pipette gun and allowed to stand for 5 minutes. Then, a few drops of the mixture were dropped on a clean silicon wafer, and the solvent was allowed to evaporate naturally. The sample was tested after it was dried. Scanning electron microscopy ( Figure 4 ) and determined that after the addition of cyclopentane, the morphology of C1 changed from a cubic block (side length 2-4μm) to a rectangular flake (side length 2-3μm, thickness 0.5μm). Such a change from a regular morphology indicates that the entire detection process is an orderly to orderly transition of an assembly.

[0080] Compared with the X-ray spectrum (surface scan) of C1, both have zinc and chlorine elements. The rectangular flakes do not contain iron and sulfur elements, but contain nitrogen elements, indicating that the granular compounds formed after C1 responds to cyclen do not contain the precursor [Cp*Fe(η 3 -tpdt)], but rather new substances containing cyclen.

[0081] Similarly, complexes C2 and C3 can also be assembled into different morphologies after being mixed with different types of polyamines in equal moles (process and conditions are the same as above). Figure 5). For example: C1 assembled into a petal-like structure with ethylenediamine, assembled into a sea urchin-like structure with 4,4'-bipyridine, C2 assembled into a thin hexagonal and square structure with 2,2'-bipyridine and 4,4'-bipyridine respectively, assembled into a three-dimensional six-leaf petal with imidazole, assembled into a three-dimensional hexagonal structure with histamine, C3 assembled into a large rectangular sheet with diethylenetriamine, assembled into a disc-like structure with imidazole, and assembled into a three-dimensional rectangle with histamine. The above results show that the response process of C1, C2 and C3 to polyamines is a process of transformation from an ordered assembly to an ordered assembly.

[0082] Example 16 X-ray single crystal diffraction test

[0083] Through the above series of studies, it is confirmed that the complex reacts with polyamines and decomposes into the precursor [Cp*Fe(η 3 -tpdt)], for the generated granular compound, we used X-ray single crystal diffraction test to determine its precise structure and clarified the entire mechanism of the iron-sulfur compound's response to polyamines. Using C1 as a template, after mixing with cyclen (in a dichloromethane solution, the final concentration was 3.3mM), the insoluble matter in dichloromethane was separated and purified by repeated centrifugation and dichloromethane washing. The compound was recrystallized by slowly adding ether (5mL) to its saturated methanol (2mL). The precise molecular structure of the complex N1 was obtained by X-ray single crystal diffraction ( Figure 6 ), is a mononuclear complex formed by cyclopentane and ZnCl2 in a 1:1 coordination, in which the four nitrogen atoms of cyclopentane are all connected to Zn 2+ To coordinate, a Cl atom on ZnCl2 and Zn 2+ The other Cl atom is freed and exists as a negative ion. In addition, there is a hydrogen bond between the cyclamenine ligand in the complex N1 and the free chlorine atom, connecting the molecules into a huge grid structure, which also corresponds to the ordered morphology in the scanning electron microscope.

[0084] Similarly, an equimolar amount of 2,2'-bipyridine was added to a dichloromethane (2mL) solution of C2 (1mmol), and the color of the solution immediately changed from purple to dark red. Then, n-hexane (5mL) was slowly added to the mixture to obtain a single crystal of the product of the reaction between C2 and 2,2'-bipyridine, and the precise structure of N2 was obtained by analysis. An equimolar amount of cyclen was added to a dichloromethane (2mL) solution of C3 (1mmol), and the color of the solution immediately changed from purple to green. The mixture was centrifuged, and the precipitated solid was washed with dichloromethane, then the solid was dissolved with methanol (2mL), and ether (5mL) was slowly added to the system, and the compound was recrystallized, and the precise structure of N3 was obtained by analysis.

[0085] The above results show that after the complex responds to polyamine, its binuclear structure decomposes into a mononuclear precursor [Cp*Fe(η 3 -tpdt)] and generate new compounds after combining with polyamines. The new compounds were characterized by X-ray single crystal diffraction technology and scanning electron microscopy structure test, which confirmed that the entire polyamine response process is an order-to-order assembly-driven process.

Claims

1. An iron-sulfur complex, characterized in that: Including one or two of the following two complexes, Complex [Cp*Fe(μ-1 κ 3 SS′:2 κ 2 SS-tpdt)ZnCl2] (referred to as C1), Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)MnCl2] (referred to as C3), Where Cp*=η 5 -C5Me5 is pentamethylcyclopentadiene; tpdt, S[CH2CH2S - ]2 is bis-mercaptoethyl sulfide.

2. A method for preparing the complex according to claim 1, characterized in that: Using mononuclear iron complexes [Cp*Fe(η 3 -tpdt)] as a precursor, which reacts with a metal salt in a reaction solvent, and after washing and drying, a complex is prepared; The metal salts include one or two of zinc chloride and manganese chloride.

3. The preparation method according to claim 2, characterized in that: The amount of the metal salt is 0.5 to 1.5 times the molar equivalent of the mononuclear iron complex, preferably 1 to 1.2 times the molar equivalent.

4. The preparation method according to claim 2, characterized in that: The reaction solvent includes one or more of dichloromethane, chloroform, tetrahydrofuran, acetonitrile, methanol and ethanol.

5. The preparation method according to claim 2, characterized in that: The reaction time includes 1-12 hours, preferably 3-6 hours; The concentration range of the mononuclear iron complex in the reaction solvent is 0.02-1.0M, preferably 0.03-0.06M.

6. Use of a complex in the specific detection of organic amines; the complex is one, two or three of the following three: Complex [Cp*Fe(μ-1 κ 3 SS′:2 κ 2 SS-tpdt)ZnCl2] (referred to as C1), Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)FeCl2] (referred to as C2), Complex [Cp*Fe(μ-1 κ 3 SSS′:2 κ 2 SS-tpdt)MnCl2](abbreviated as C3).

7. The use according to claim 6, characterized in that: The concentration range of the complex in the organic amine solution is 0.23-3.3 mM, preferably 0.33-1 mM.

8. The use according to claim 6, characterized in that: The detection means include qualitative detection or quantitative detection, wherein the qualitative detection includes one or more of ultraviolet spectrum detection, naked eye detection and cyclic voltammetry test, and the quantitative detection includes differential pulse voltammetry test; It is a method for the specific detection of organic amines driven by the ordered-to-order transition of iron-sulfur-based assemblies.

9. The use according to claim 6, characterized in that: The types of organic amines include one or more of polyamines and monoamines; The types of polyamines include ethylenediamine, 1,2-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, hexamethylenediamine, spermidine, spermine, diethylenetriamine, triethylenetetramine, N,N'-dimethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, pentamethyldiethylenetriamine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, 1,4,7-triazacyclononane, cyclopentane, imidazole, histamine, one or more of 2,2'-bipyridine and 4,4'-bipyridine; The types of the monoamines include one or more of pyridine, cyclohexylamine, n-propylamine, n-hexylamine, isopropylamine, tert-butylamine, diethylamine, triethylamine, N,N-diisopropylethylamine, piperidine, benzylamine, phenethylamine and aniline.

10. The use according to claim 9, characterized in that: During detection, the concentration of the polyamine in the solution is 0.05-2.0 mM, preferably 0.4-0.6 mM; During detection, the concentration of the monoamine in the solution is 1.0-15.0 mM, preferably 2-5 mM.